Intelligent acquisition model of traffic congestion information in the vehicle networking environment based on multi-sensor fusion. (5th August 2019) - Jiang, Kun; Su, Dan; Zheng, Yanfu
Aiming at the problems of low bandwidth, poor anti-interference ability and low-detection accuracy of traditional multi-path coherent vehicle network model, an intelligent acquisition model of traffic congestion information in vehicle network environment based on multi-features is proposed. The model clusters the traffic congestion information in the vehicle network and uses the multi-sensor fusion identification method to mine the traffic flow. In the vehicle networking environment, the vehicle traffic congestion information is analysed by information fusion theory, cross-fusion, text information, location information, image, audio, video and other information-aware technologies, and the coherent matching filter detector is used to realise the detection of traffic congestion information. And data collection, combined with knowledge base and database construction, is used to achieve intelligent collection and storage of traffic congestion information. The simulation results show that the model has high traffic congestion information acquisition accuracy and good feature matching ability, improves the intelligent acquisition ability, and detects the traffic congestion information in the vehicle network environment, thus guiding traffic scheduling.